Advanced Control of Future Electric Propulsion Systems for Passenger Vehicles - Subbiah, Vignesh Arumugam; Nandivada, Yashasvi (My University, 2018)
Electric Vehicles (EVs) have been around since the 19th century,in fact the EVs were quite popular in that time period and a good number of them were sold during the 1900s but due to the advancement of gasoline engines and the invention of the electric starters for gasoline engines, vehicles powered with internal combustion engines began to dominate the market, thereby the trend for EVs declined until the early 2000s. From the early 2000s on-wards the market share of EVs has begun to rise due to the price rise of gasoline, enactment of stringent environmental policies and advent of cost effective manufacturing capabilities for EVs. The increased demand and environmental benefits of EVs are pushing the automotive companies to invest in the research and development for the Electric Vehicles to initiate the mitigation of global warming. As the technology is moving towards EVs there is also an increased need to set goals to mitigate the road accidents and improve the vehicle and traffic safety. As a matter of fact it could be stated that Electric propulsion systems have advantages over the conventional propulsion systems since the former has a high-power density, short response time and a better controllability. However, with the ongoing trends, for future vehicles with more sophisticated safety functions, the demand for controllability will be higher. Also new driving cycles used for energy consumption, correlating better with normal driving, will put higher demands on drive-train control. Thus the main objective of this thesis is to study and implement potential measures to improve controllability of electric drivetrains, in the view of ongoing development trends. As part of addressing the objective, it is envisioned to analyse the strengths and weaknesses in the present and future systems & the possibility of developing principles, methods and solutions to improve the control accuracy, response time, predictability and reliability is investigated. The first phase of the thesis majorly involved developing a state of the art drive-train based on the electric propulsion technology available in the current market. This model, developed in SIMULINK, is then validated against the real world data. This part of the thesis also involves establishing use cases and sub-system performance targets for a comparative study at a later point of the thesis. The second phase of the thesis involves establishing a relation between the control parameters and sub system performance targets, which would then be the principles of improvement. Subsequently, based on the ndings from the technology trends, a Future Drive-train is also proposed during this phase. The third phase involves developing the Future Drive-train and implementing the proposed principles, via a design of experiments approach, on the Future Drive-train to obtain an Optimised Future Drive-train. On carrying out the process of optimisation on the Future drive-train an Optimised Future drive-train consisting of a Switched Reluctance Motor (SRM) of 93 kW is obtained. The power of the developed SRM is within 7% of the state of the art motor. In terms of acceleration performance (rise time from 0 to 90% of reference velocity) the developed Optimal Future drive-train lags with respect the state of the art drive-train by 2%. This speed dependent characteristic is observed for a 0-35 kmph Step Reference Input. In terms of performance on drive cycles the Optimal Future drive-train, at worst, has a 3% greater deviation from reference velocity when compared to the state of the art drive-train due to its falling power characteristics at higher speeds. In terms of acceleration performance on a transient friction surface, the Optimal Future drive-train performs better on all counts due to the reduction of reflected load inertia stemming from a higher gear ratio.The developed principles of improvement are inline with the expectations to tackle the controllability issue of the future drive-trains.
Keywords: Fastkroppsmekanik; Farkostteknik; Transport; Solid mechanics; Vehicle Engineering; Transport